Heparan sulfate proteoglycan deficiency up-regulates the intracellular production of nitric oxide in Chinese hamster ovary cell lines - Lucena, Sheyla Varela [UNIFESP] (2018)
We investigated the role of glycosaminoglycans (GAGs) in the regulation of endothelial nitric oxide synthase (eNOS) activity in wild-type CHO-K1 cells and in xylosyltransferase-deficient CHO-745 cells. GAGs inhibit the integrin/FAK/PI3K/AKT signaling pathway in CHO-K1 cells, decreasing the phosphorylation of eNOS at Ser1177. Furthermore, in CHO-K1 cells, eNOS and PKC are localized at sphingolipid- and cholesterol-rich domains in the plasma membrane called caveolae. At caveolae, PKC activation stimulates the phosphorylation of eNOS on Thr495, resulting in further inhibition of NO production in these cells. In our data, CHO-745 cells generate approximately 12-fold more NO than CHO-K1 cells. Increased NO production in CHO-745 cells promotes higher rates of protein S-nitrosylation and protein tyrosine nitration. Regarding reactive oxygen species (ROS) production, CHO-745 cells show lower basal levels of superoxide (O-2(-)) than CHO-K1 cells. In addition, CHO-745 cells express higher levels of GPx, Trx1, and catalase than CHO-K1 cells, suggesting that CHO-745 cells are in a constitutive nitrosative/oxidative stress condition. Accordingly, we showed that CHO-745 cells are more sensitive to oxidant-induced cell death than CHO-K1 cells. The high concentration of NO and reactive oxygen species generated by CHO-745 cells can induce simultaneous mitochondrial biogenesis and antioxidant gene expression. These observations led us to propose that GAGs are part of a regulatory mechanism that participates in eNOS activation and consequently regulates nitrosative/oxidative stress in CHO cells.